Skill policies for Scotland - James Joseph Heckman; Dimitriy V. Masterov (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper argues that skill formation is a life-cycle process and develops the implications of this insight for Scottish social policy. Families are major producers of skills, and a successful policy needs to promote effective families and to supplement failing ones. Targeted early interventions have proven to be very effective in compensating for the effect of neglect. Improvements in traditional measures of school quality, tuition subsidies, company-sponsored and public job training are unlikely to be as effective. We review the evidence and present several policy recommendations.
Keywords: I21; J31; I28; I22; 330; Qualifikation; Lernprozess; Lebenszyklus; Bildungsinvestition; Familienpolitik; Bildungspolitik; Bildungsertrag; Schottland; Welt; England; Vereinigte Staaten